Mapping the core journals of the physical therapy literature - Fell, Dennis W; Burnham, Judy F; Buchanan, Melanie J; Horchen, Heidi A; Scherr, Joel A (Journal of the Medical Library Association, 2011)
The purpose of this study was to identify (1) core journals in the literature of physical therapy, (2) currency of references cited in that literature, and (3) online databases providing the highest coverage rate of core journals. Data for each cited reference in each article of four source journals for three years were recorded, including type of literature, year of publication, and journal title. The journal titles were ranked in descending order according to the frequency of citations and divided into three zones using Bradford's Law of Scattering. Four databases were analyzed for coverage rates of articles published in the Zone 1 and Zone 2 journals in 2007. Journal articles were the most frequently cited type of literature, with sixteen journals supplying one-third of the cited journal references. Physical Therapy was the most commonly cited title. There were more cited articles published from 2000 to 2007 than in any previous full decade. Of the databases analyzed, CINAHL provided the highest coverage rate for Zone 1 2007 publications. Results were similar to a previous study, except for changes in the order of Zone 1 journals. Results can help physical therapists and librarians determine important journals in this discipline.